2019
DOI: 10.3390/f10110959
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Microscopy of Alnus glutinosa Pollen Fluorescence Peculiarities

Abstract: Alnus glutinosa is an important woody plant in Lithuanian forest ecosystems. Knowledge of fluorescence properties of black alder pollen is necessary for scientific and practical purposes. By the results of the study, we aimed to evaluate possibilities of identifying Alnus glutinosa pollen fluorescence properties by modeling ozone effect and applying two different fluorescence-based devices. To implement the experiments, black alder pollen was collected in a typical habitat during the annual flowering period in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 39 publications
(79 reference statements)
0
4
0
Order By: Relevance
“…The inner layers of the exine of Pinus pollen strictly control the permeability of carbohydrates to the central part, it is likely that there is also a serious barrier to the entry of water, alcohols, ampholytes and cations into the pollen [ 30 ], and compounds of higher molecular weight, including phenolic compounds, can enter only after rupture of the exine [ 8 , 57 ]. However, pollen stored for a long time loses some of its properties [ 58 ], the ability of pollen to release cytoplasmic contents to the environment weakens [ 39 ]. Forced release of Pinus pollen content into the environment requires stressful conditions: pressure and processing of pollen with inorganic acids, but even after Pinus pollen bursts, the spilled content is likely to remain enveloped in the intina layer [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The inner layers of the exine of Pinus pollen strictly control the permeability of carbohydrates to the central part, it is likely that there is also a serious barrier to the entry of water, alcohols, ampholytes and cations into the pollen [ 30 ], and compounds of higher molecular weight, including phenolic compounds, can enter only after rupture of the exine [ 8 , 57 ]. However, pollen stored for a long time loses some of its properties [ 58 ], the ability of pollen to release cytoplasmic contents to the environment weakens [ 39 ]. Forced release of Pinus pollen content into the environment requires stressful conditions: pressure and processing of pollen with inorganic acids, but even after Pinus pollen bursts, the spilled content is likely to remain enveloped in the intina layer [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The use of clusters for the analysis of fluorescent aerosol has supplemented the results of our previous studies [13,47] and provided new knowledge on the use of the automatic detector for operational information on airborne pollen concentration. Occasionally, authors [5,6,13] encounter unexplained cases due to specific identification issues related to pollen features.…”
Section: Discussionmentioning
confidence: 95%
“…Our openness strategy allows anyone to benefit from laboratory experiments data of tested pollen with the Rapid-E device [ 31 , 32 ]. The developed digital data library is valuable material [ 13 , 47 ] and allows successfully improve the knowledge on the features of particles present in the atmospheric bioaerosol. This study has revealed that the clustering of pollen data in the stage of identification is valuable in various aspects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation